Effect of consumption of animal milk compared to infant formula for non-breastfed/mixed-fed infants 6–11 months of age: a systematic review (protocol). Issue 2 (12th February 2021) - Imdad, Aamer; Ehrlich, Julie Melissa; Catania, Joseph; Tanner-Smith, Emily; Smith, Abigail; Tsistinas, Olivia; Bhutta, Zulfiqar Ahmed
Abstract : Introduction: Prevalence rates of breastfeeding remain low even though the World Health Organization (WHO) and the American Academy of Pediatrics recommend exclusive breast feeding for the first 6 months of life in combination with appropriate complementary feeding beyond six 6 months of age. There have been several studies that address the implication of drinking animal milk and/or infant formula on children's health and development when breast feeding is not offered during the first year of life. Vast improvements have been made in infant formula design, which may increase its benefits compared with animal's milk. The objective of this review is therefore to synthesise the most recent evidence on the effects of the consumption of animal milk compared with infant formula in non-breastfed or mixed breastfed infants aged 6–11 months. Methods and analysis: We will conduct a systematic review and meta-analysis of studies that assessed the effect of animal milk compared with formula or mixed-fed (breastmilk and formula) on infants aged 6–11 months. The primary outcomes of interest include anaemia, gastrointestinal blood loss, weight for age, height for age and weight for height. We will include randomised and non-randomised studies with a control group. We will use the Cochrane risk of bias tools to assess the risk of bias. We will use meta-analysis to pool findings if the identified studies are conceptually homogenous and data are available from more than one study. We will assess the overall quality of evidence using the Grading of Recommendations Assessment, Development, and Evaluation approach. Ethics and dissemination: This is a systematic review, so no patients will be directly involved in the design or development of this study. The findings from this systematic review will be disseminated to relevant patient populations and caregivers and will guide the WHO's recommendations on formula consumption versus animal milk in infants aged 6–11 months. Trial registration number: CRD42020210925.